Kalos Kagathos - on Personal Values in Sport - Jan Czechowski (Nicolaus Copernicus University in Toruń, 2014)
An object of the reflection in herein text is the reference to constitutive values of good and beauty in sport, as well as personal values in general. A specific nature of a man is described here: will by which a man controls his reactions, attitudes and efforts in execution of some goals and actions. It is represented by courage, persistence and consequence. It is therefore the grounds and enables reaching the values by a person who faces internal or external obstacles on its way. Raising the issue of personal values, in particular in reference to young sportsmen, one cannot omit the term of fair play. In general the rule defines the struggle for victory but not at all costs, unquestionable referee judgments, honesty, immediacy and maintenance of unbroken, law-abiding attitude in case where others do not follow the fair play requirements. A contestant must then be distinguished by respect for team colleague despite the win or loss and recognition of him or her as a essential partner in achieving overriding sport ideals, respect for a referee represented by the strive to cooperation during competition and afterwards. Personal values of a man actively involved in sport undergoings result from the level of recognition of self-esteem as a person. Knowing his or her own, represented values, pros nut also awarnes of cons a person becomes ready for a fight against obstacles and capable of withstanding stalemate situations. Such person would perceive reality from the bright side and is independent to the large extend, as well as executes own goals. A sportsman - as presented in the text - with considerable level of self-esteem is not only a cheerful and an open man but also a man of substantial personal values, as well as meets the requirements defined by the sports arena.